Perilaku Beban-Perpindahan Aksial Pre-Buckling dan Post-Buckling pada Struktur Kolom Elastis - Sumirin, Sumirin (Department of Civil Engineering, Diponegoro University, 2014)
The analysis of column buckling is generally based on the analysis of linear eigenvalue problem to obtain the buckling load. In the linear analysis we do not know the load-displacement behavior especially after buckling occurs. This research studied the behavior of the elastic column on the stage pre-buckling and post-buckling by finite gemetrically nonlinear of finite element method. Difficulties in equilibrium problem at around the point of buckling load solved by using the Newton-Raphson incremental method with constant arc- length technique. To generate the initial touch of buckling columns are very small lateral load or by providing the initial lateral deformation is very small. Axial load-displacement curve column finite element analysis results compared to the results of previous reseacher. An axial load-displacement curve bilinear proposed in this study.